What Does Robert Lewandowski have in Common with Andrzej Duda? About the Knowledge of Famous Poles among Ukrainians Learning Polish (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
This article is devoted to the analysis of the knowledge of Polish culturemes concerning famous Poles by Ukrainians learning Polish as a foreign language. It consists of two parts. The first presents theoretical issues concerning culture and language and culturemes. The second analyzes the results of survey research. The aim is to show the relationship between the group of respondents and their knowledge of Polish culture.